2015
DOI: 10.3109/13880209.2015.1052885
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of major phenolics fromLaunaea spinosaand their protective effect on HepG2 cells damaged witht-BHP

Abstract: The major phenolic compounds isolated from L. spinosa displayed a significant cytoprotective effect against oxidative stress, leading to maintenance of the normal redox status of the cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…These results indicated that polyphenol components of the HB extracts have an effect on the cell viability in HepG2 cells induced by t-BHP. This finding is supported by another study where phenolic compounds displayed protective effects against oxidative stress, leading to the maintenance of a normal redox state of the cell [ 22 ]. HBK and HBC showed increased cell viabilities in a dose-dependent manner, although 30 µg/mL of HBK did not show a significant increase in cell viabilities.…”
Section: Discussionsupporting
confidence: 61%
“…These results indicated that polyphenol components of the HB extracts have an effect on the cell viability in HepG2 cells induced by t-BHP. This finding is supported by another study where phenolic compounds displayed protective effects against oxidative stress, leading to the maintenance of a normal redox state of the cell [ 22 ]. HBK and HBC showed increased cell viabilities in a dose-dependent manner, although 30 µg/mL of HBK did not show a significant increase in cell viabilities.…”
Section: Discussionsupporting
confidence: 61%
“…The exception was found to be natural resistance of this fungus to these extracts (Okwori et al, 2008). The antifungal activities and cytoprotective effect of medicinal plants are attributed to the presence of flavonoids, tannins and phenolic compounds (Abdallah et al, 2015). The traditional healers make use of water primarily as a solvent, but our study showed that, different extracts of both plants and latex were much better and powerful.…”
Section: Antimicrobial Activitymentioning
confidence: 60%
“…Many of Launaea species (family Asteracea) are used in folk medicine as hepatoprotective, bitter stomachic, for treating skin diseases, and reported to have antitumor, insecticidal and cytoprotective activities (El-Bassuony andAbdel-Hamid, 2006 andKhan et al, 2012). This genus is rich in different secondary metabolites, such as terpenoids (Abdel Fattah et al, 1990), phenolic compounds (Abdallah et al, 2015) and coumarins (El-Bassuony and Abdel-Hamid, 2006). Abdallah et al (2015) reported that some of Launaea species are used traditionally to treat liver oxidative stress.…”
Section: Osmoregulation and Antimicrobial Activity Of Two Egyptian Trmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells. To evaluate hepatotoxicity induced by t-BHP, alanine aminotransferase (ALT) and aspartate aminotransferase (AST) activities were measured using the ALT and AST kit (Biovision, CA) as previously described (Abdallah et al 2016). HepG2 cells were seeded into 24-well plates (2.5 3 10 5 cells per well) and incubated for 24 h. The cells were treated with various concentrations of AFR, AFP, quercetin and DMSO for 24 h, and then with 200 lM t-BHP for 3 h. The cells were then washed with DPBS and harvested by centrifugation at 2,870 3 g for 5 min at 4C.…”
Section: Measurement Of Alt and Ast Activities In Hepg2mentioning
confidence: 99%